Challenges of CAFTA : Maximizing the Benefits for Central America - Jaramillo, Carlos Felipe (Washington, DC : World Bank, 2012)
The report provides a preliminary assessment of DR-CAFTA (the Dominican Republic and Central American Free trade Agreement), with particular attention to three key themes: (1) expected trade and non-trade benefits, (2) actions that Central American countries need to pursue to capitalize optimally on the new opportunities, and (3) identification of the population groups that may require assistance to adapt to a more competitive environment. The Introductory Chapter reviews the main findings of the report. Chapter 2 places DR-CAFTA in the historical context of the economic reforms that Central America has been undertaking since the late 1980s. Chapter 3 provides a summary overview of the recently negotiated DR-CAFTA. Chapter 4 reviews various analyses that assess the potential impacts of DR-CAFTA in Central American countries. Chapter 5 focuses on the identification of potentially affected populations from the easing of trade restrictions in sensitive agricultural products and analyzes policy options to assist vulnerable groups. Chapter 6 reviews evidence related to key macroeconomic implications of DR-CAFTA, namely the potential revenue losses and effect on the patterns of business-cycle synchronization. Chapter 7 reviews evidence from each Central American country in the areas of trade facilitation, institutional and regulatory reforms, and innovation and education, in order to identify key priorities for the complementary agenda for DR-CAFTA.